Human Resource Management for Gaining a Competitive Advantage - Poopatanapong, Kaewta (Journal of Multidisciplinary in Humanities and Social Sciences, 2020)
The organization's operations under the rapidly changing economic, social, political, and technological environment in the globalization era. Both public and private organizations aim to increase efficiency. Effectiveness and productivity in order to have a competitive advantage, so it is a challenge for management to manage the limited resources to maximize benefits. Resources such as money, materials, management and human resources, etc. But among those resources, human resources are the most important factor because human resources are managing other factors. Take care to fix any errors that occur. Choose the right technology for use in work and production for the benefit of the organization. Strategic human resource management has changed from a proactive approach to a more proactive systematic analysis and planning for all human resource management activities is linked to the organization's strategy or goals. In order to acquire the human resources that are capable and suitable for the organization Human resource development to be creative and innovative that will add value to products or businesses to give the organization a competitive advantage in the future.